Correction: MSLN gene silencing has an anti-malignant effect on cell lines overexpressing mesothelin deriving from malignant pleural mesothelioma. - Ombretta Melaiu; Justin Stebbing; Ylenia Lombardo; Elisa Bracci; Norihisa Uehara; Alessandra Bonotti; Alfonso Cristaudo; Rudy Foddis; Luciano Mutti; Roberto Barale; Federica Gemignani; Georgios Giamas; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0085935.].